Informe sobre la segregación social e inmigración en el municipio de Madrid - Jeannin, Méryl; Alcolea Moratilla, Miguel A. (M+A. Revista Electrónica de Medioambiente, 2006)
This report addresses two phenomenons which are certainly not new but which gained in magnitude during the last decades: social segregation and immigration. The situation is akin to what is taking place in most big European cities. However, in the present case, we limited ourselves to the municipality of Madrid. Social segregation in this city is clearly delimited according to a diagonal separating the North/North West – with well-off areas, some of which making the exception- from the East/South- East/South, with a lower social class. Immigration is a relatively new phenomenon in Madrid pertaining to the magnitude it reached. Although immigration has been present for a long time now, the percentage represented by foreigners has never been as high as it is now. The majority of immigrants come from South America, Morocco and Rumania. The biggest minority is represented by Ecuadorians (27.5%). These two phenomenons are expressed simultaneously in the urban landscape. Immigrant areas correspond to classes with a low standard of living from the South/South-East of the city.